2020
DOI: 10.1016/j.sleep.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Sleep characteristics in health workers exposed to the COVID-19 pandemic

Abstract: Introduction The development of sleep disorders, and specifically insomnia, has been linked to the exposure to different stressors. In this line, Coronavirus disease 2019 (COVID-19) outbreak caused by the new coronavirus SARS-CoV-2, has caused a huge impact on our environment, and has exposed healthcare workers to an unprecedented threat. In this study, we try to assess sleep quality and the development of sleep disorders in health personnel directly dedicated to the care of COVID-19 patients at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
5
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 24 publications
6
98
5
5
Order By: Relevance
“…and 27.3% of medical workers dealing with COVID-19 patients in the present study. Compared with our findings, previous reports found a higher prevalence (38-59%) of nightmares in frontline health-care workers during the COVID-19 pandemic (Giardino et al, 2020;Herrero San Martin et al, 2020;Tu et al, 2020). The discrepancy may mainly come from differences in frequency required for diagnosing a nightmare, which was not described or was defined as the response of "yes" of "presenting nightmare symptoms" in some studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…and 27.3% of medical workers dealing with COVID-19 patients in the present study. Compared with our findings, previous reports found a higher prevalence (38-59%) of nightmares in frontline health-care workers during the COVID-19 pandemic (Giardino et al, 2020;Herrero San Martin et al, 2020;Tu et al, 2020). The discrepancy may mainly come from differences in frequency required for diagnosing a nightmare, which was not described or was defined as the response of "yes" of "presenting nightmare symptoms" in some studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Nightmares were one of parasomnias, which present as vivid dreams containing negative emotions during rapid eye movement (REM) with usually subsequent awakenings (Sateia, 2014). During the COVID-19 pandemic, nightmares were found in 38-59% (Giardino et al, 2020;Herrero San Martin et al, 2020;Tu et al, 2020) of healthcare workers at the frontline, higher than those in non-healthcare workers (Herrero San Martin et al, 2020). Nightmares were related to depression symptoms, anxiety disorder, psychiatric diagnosis, and neuroticism personality trait in the general public (Nakajima et al, 2014;Sandman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Salari et al [ 8 ] reviewed 7 cross-sectional studies from Asia and the Middle East conducted among nurses and physicians prior to June 24, 2020, and they reported a prevalence of sleep disturbances of 34.8% and 41.6% in nurses and physicians, respectively. Additionally, several other studies reported on sleep loss in health care workers from countries such as Oman [ 9 ], Bahrain [ 10 ], and Spain [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 presents the collected data with corresponding interpretation towards analysed sleep quality in healthcare givers. The analysed data indicate that working with COVID-19-affected patients is associated not only with a poorer sleep quality and insomnia symptoms, but also with mental health risks such as increased stress and burnout as well as a strong predisposition to mental disorders such as depression and anxiety [56,57,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Sleep Quality In the Healthcare Givers Under The Covid-19 Pandemic Conditionmentioning
confidence: 99%